Comparative analysis of voice changes after thyroidectomy; mass versus individual ligation of superior thyroid artery with reference to identification of external branch of superior laryngeal nerve - Samdani, Sunil; Dudi, Shweta; Mobarsa, Veena (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The external branch of the superior laryngeal nerve innervates the cricothyroid muscle to promote lengthening and thinning of the vocal fold, thus increasing voice pitch. The close relation with the superior thyroid vessels puts the external branch of the superior laryngeal nerve in risk every time the superior pole of the thyroid is dissected. Methods: : This randomized controlled study was undertaken at SMS Medical College, Jaipur between February 2013 to November 2014 to evaluate the impact of isolating and ligating the superior thyroid vessels near the upper pole of the gland as compared to conventional mass ligation of the superior pole regarding external branch of superior laryngeal nerve injury in hemi or subtotal thyroidectomy. Total 120 patients were taken and divided into two groups A and B. Group A including mass ligation of superior pole of thyroid and group B includes individual ligation of superior thyroid vessels. Results: Our study observed normal voice in 51 cases (85%) in individual ligation of superior thyroid vessel group and 27 cases (45%) in mass ligation group on auditory perceptual test by GRBAS scale one month postoperatively. Normal electromyography findings after 1 month post-operatively was observed in 57 cases (95%) in individual ligation group as compared to 40 cases (66.67%) in mass ligation group. Conclusions: Our study conclude that careful ligation of superior thyroid vessels is a safe technique to preserve the external branch of superior laryngeal nerve than mass ligation of superior pole of thyroid.